2015
DOI: 10.1186/s12893-015-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery (ERAS) protocols for colorectal cancer in Japan

Abstract: BackgroundJapan has one of the highest five-year relative survival rates for colorectal cancer in the world, with its own traditions of perioperative care and a unique insurance system. The benefits of enhanced recovery after surgery (ERAS) protocols in the Japanese population have yet to be clarified.MethodsWe evaluated 352 consecutive cases of colorectal cancer resection at Tokyo Metropolitan Bokutoh Hospital between July 2009 and November 2012. Of these, 95 cases were performed according to traditional prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
2
25
1
4
Order By: Relevance
“…The patients should be encouraged to start on the oral intake of clear fluids, and normal diet following surgery [15]. Oral fluid intake was started immediately after (Huibers et [17][18][19][20]. In the present study, peri-and post-operative administrated intravenous fluids were significantly lower in the ERAS group.…”
Section: Discussionmentioning
confidence: 51%
“…The patients should be encouraged to start on the oral intake of clear fluids, and normal diet following surgery [15]. Oral fluid intake was started immediately after (Huibers et [17][18][19][20]. In the present study, peri-and post-operative administrated intravenous fluids were significantly lower in the ERAS group.…”
Section: Discussionmentioning
confidence: 51%
“…There have been conflicting results from many studies regarding the relationship between colorectal surgery hospital volumes and LOS 3,7,8,11–31 . Chowdhury et al, in their comprehensive systematic review, analysed 127 studies that examined surgical outcomes including LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Since Adams et al 9 in 1973 and Lufte et al 10 in 1979 reported a link between provider volume and successful surgical outcomes, provider volume has been used as a surrogate measure of hospital quality. Evidence of an association between hospital or surgeon cancer surgery volume and better patient outcomes has been mixed; 3,7,8,11–31 however, previous analyses have had important limitations. A 2002 review that examined seven statistical modelling techniques used to assess association between patient factors and LOS in a cardiovascular setting found that choice of model influenced the conclusion of the analyses.…”
mentioning
confidence: 99%
“…In addition, research analyzing the deployment of ERAS among patients who underwent colorectal surgery concluded that the need for infusion of liquids and hospitalization time decreased (24) .…”
Section: Discussionmentioning
confidence: 99%